Surgery for Mesothelioma After Radiation Therapy (SMART); A Single Institution Experience - Breen, William G.; Garces, Yolanda I.; Olivier, Kenneth R.; Park, Sean S.; Merrell, Kenneth W.; Nichols, Francis C.; Peikert, Tobias D.; Molina, Julian R.; Mansfield, Aaron S.; Roden, Anja C.; Blackmon, Shanda H.; Wigle, Dennis A. (Frontiers in Oncology, 2020)
Background: The optimal treatment sequence for localized malignant pleural mesothelioma (MPM) is controversial. We aimed to assess outcomes and toxicities of treating localized MPM with neoadjuvant radiation therapy (RT) followed by extrapleural pneumonectomy (EPP). Methods: Patients were enrolled on an institutional protocol of surgery for mesothelioma after radiation therapy (SMART) between June 2016 and May 2017. Eligible patients were adults with MPM localized to the ipsilateral pleura. Patients underwent staging with PET/CT, pleuroscopy, bronchoscopy/EBUS, mediastinoscopy, and laparoscopy. Five fractions of RT were delivered using intensity modulated radiation therapy (IMRT), with 30 Gy delivered to gross disease and 25 Gy to the entire pleura. EPP was performed 4-10 days following completion of RT. Results: Five patients were treated on protocol. Median age was 62 years (range 36-66). Histology was epithelioid on initial biopsy in all patients, but one was found to have biphasic histology after surgery. Three patients had surgeon-assessed gross total resection, and two had gross residual disease. While all patients were clinically node negative by pretreatment staging, three had positive nodal disease at surgery. Patients were hospitalized for a median 24 days (range 5-69) following surgery. Two patients developed empyema, one of whom developed respiratory failure and subsequently renal failure requiring dialysis, while the other required multiple surgical debridements. Two patients developed atrial fibrillation with rapid ventricular response after surgery, one of whom developed acute respiratory distress requiring intubation and tracheostomy. At last follow-up, one patient died at 1.4 years after local and distant progression, two were alive with local and distant progression, and the remaining two were alive without evidence of disease at 0.1 and 2.7 years. Median time to progression was 9 months. Three patients received salvage chemotherapy. Conclusions: SMART provided promising oncologic outcomes at the cost of significant treatment related morbidity. Due to the significant treatment associated morbidity and favorable treatment alternatives, we have not broadly adopted SMART at our institution.